2007
DOI: 10.1007/s11104-007-9344-z
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination of agricultural weeds is promoted by the butenolide 3-methyl-2H-furo[2,3-c]pyran-2-one under laboratory and field conditions

Abstract: Here we report that a synthesised form of a naturally occurring chemical (a butenolide, 3-methyl-2H-furo[2,3-c]pyran-2-one) found in smoke can stimulate seedling emergence of the economically important weed species Avena fatua L. (Poaceae), Arctotheca calendula (L.) Levyns (Asteraceae), Brassica tournefortii Gouan (Brassicaceae), and Raphanus raphanistrum L. (Brassicaceae) under field conditions at rates equivalent to 2-20 g/ha a.i. The butenolide also stimulates germination of freshly collected seeds from wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 31 publications
3
114
0
7
Order By: Relevance
“…Butenolide was a very active dormancy breaking factor at very low concentrations (10 -8 M) and could remove completely or partially deep dormancy in seeds at 15-25°C. Fully dormant seeds of A. fatua were more sensitive to butenolide than partially dormant seeds from the United Kingdom (Daws et al 2007) and Australia (Stevens et al 2007). Similar effects of smoke-water and butenolide on seed germination were observed in experiments with Asteraceae (Merritt et al 2006) and some agricultural plants (Daws et al 2007;Stevens et al 2007).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Butenolide was a very active dormancy breaking factor at very low concentrations (10 -8 M) and could remove completely or partially deep dormancy in seeds at 15-25°C. Fully dormant seeds of A. fatua were more sensitive to butenolide than partially dormant seeds from the United Kingdom (Daws et al 2007) and Australia (Stevens et al 2007). Similar effects of smoke-water and butenolide on seed germination were observed in experiments with Asteraceae (Merritt et al 2006) and some agricultural plants (Daws et al 2007;Stevens et al 2007).…”
Section: Discussionmentioning
confidence: 52%
“…It had a greater capacity to overcome dormancy in partly after-ripened than in freshly harvested seeds. Stevens et al (2007) observed that both smoke-water and butenolide stimulated germination of freshly harvested but only partially that of dormant seeds of A. fatua from Australia. In another study, smoke-water inhibited germination but butenolide only partially stimulated germination of dry stored A. fatua seeds collected in the United Kingdom (Daws et al 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Smoke water (20 l) was prepared from combustion of agricultural feed straw (oaten hay) 43 using the apparatus previously described 18 . Smoke water (2 l) was filtered (32 cm, Whatman No.…”
Section: A Manglesii Bioassaymentioning
confidence: 99%
“…Since the identification of KAR 1 , several diverse species have been classified as responding positively to karrikins. These include the arable weeds Brassica tournefortii and Sisymbrium orientale (Brassicacaeae) (Stevens et al 2007), and Avena fatua and Sorghum halepense (Poaceae) (Daws et al 2007). A recent study of the effects of smokewater and KAR 1 on seed germination of 13 species from South China identified only one (Aristolochia debilis; Aristolochiaceae) as responding positively to 1 nM KAR 1 or more (Zhou et al 2014).…”
Section: Seed Germination Responses To Karrikinsmentioning
confidence: 99%
“…maternal life history and wet-dry cycling regimes) that influence physiological seed dormancy in turn affect the capacity of seed to respond to karrikins (Long et al 2010(Long et al , 2011. Indeed, varying degrees of physiological seed dormancy between batches of seed from the same species can lead to apparently opposite responses to karrikins (Stevens et al 2007). It is also possible that 'nonresponsive' species have incompatible perception machinery, perhaps because, as discussed below, the relevant receptor protein has undergone selection to detect compounds other than karrikins.…”
Section: Seed Germination Responses To Karrikinsmentioning
confidence: 99%